Pancasila as the Industrial Revolution 4.0 Paradigm - Syafa Adinda; Masduki Asbari (AGUSPATI RESEARCH INSTITUTA, 2022)
This scientific article aims to examine how important Pancasila is to the impact of the 4.0 revolution at this time. The influence of the 4.0 industrial revolution is not only felt by a certain field, but also has an impact on all aspects of human life, from business, economic, social and cultural aspects, even to the industrial world. The more frequent the communication technology that began to emerge with the addition of more sophisticated features and in a very short time has been able to attract a very large number of customers as well. The issue of the development of this era is followed by the impact of weakening the nation's character and resulting in values that are not manifested in the nation's morals, so a proper development reorientation is needed referring to the state philosophy, namely Pancasila which acts as a paradigm in development to provide views of ethical principles for all aspects of life.